Brain-inspired global-local learning incorporated with neuromorphic computing - Yujie Wu; Rong Zhao; Jun Zhu; Feng Chen; Mingkun Xu; Guoqi Li; Sen Song; Lei Deng; Guanrui Wang; Hao Zheng; Songchen Ma; Jing Pei; et al. (Nature Communications, 2022)
Global and local learning represent two distinct approaches to artificial intelligence. In this manuscript, Wu et al present a hybrid learning strategy, drawing from elements of both approaches, and implement it on a co-designed neuromorphic platform.